ABORIGINALS’ RACIAL INEQUALITY AND LINGUISTIC DISPLACEMENT IN THE POEM "THEY ASK ME: ‘WHO AM I?’” - Gazzaz, Rasha; Elyas, Tariq (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
Through a close reading of “They ask me: ‘Who am I?’’' poem, this paper examines the themes of racial inequality and linguistic displacement of the oppressed race of the Australian Aboriginals, specifically the lost generation as voiced in the poem. Adopting the theoretical frameworks of Kroskrity that focus on the linguistic racism and white supremacy, the authors analytically aim to explore covert linguistic racism through the poem’s narrative. In addition, this paper conveys the representation of race and colonial powers by conveying the exclusion and discrimination the Aborigines faced since the 18th century. It highlights the ‘White Supremacy’ (concerning politics, culture, and linguistics) and the desperate measures the white settlement took to complete the erasure of the linguistic and culture of the minority group of the Aboriginal people. The poem highlights the unspoken voices of the lost generation through the poet's heartfelt agony with his encounter with the history of Aboriginals and their racial and linguistic oppression.